The prevalence of anti-thyroid peroxidase antibodies in subclinica and clinical hypothyroid patients - C.A., Jayashankar; S., Avinash; B., Shashidharan; Sarathi, Vijaya; K.R., Shruthi; D., Nikethan; J., Harshavardhan (International Journal of Research in Medical Sciences, 2017)
Background: Subclinical hypothyroidism is a state of mild thyroid failure and is essentially a laboratory diagnosis with elevated serum thyroid stimulating hormone (TSH) and a normal free thyroxine (FT4) concentration. The main objective of study is to evaluate the prevalence of anti-thyroid peroxidise (anti-TPO) antibodies among patients with clinical and subclinical hypothyroidism. Methods: A prospective study was conducted involving 50 patients with biochemical evidence of hypothyroidism. Subclinical hypothyroidism was defined as thyroid stimulating hormone (TSH) >5.0 µIU/ml with normal FT4 and clinical hypothyroidism as free thyroxine (FT4) and high TSH. A detailed history, clinical examination, and investigations comprising of complete haemogram, fasting plasma glucose, fasting FT4, TSH, anti-TPO antibodies and lipid profile were done for all the patients. Results: Out of 50 cases, 28 subjects had clinical hypothyroidism (25 females and 3 males) and 22 had subclinical hypothyroidism (14 females and 8males). Among the 50 subjects with clinical and subclinical hypothyroidism, 33 were anti-TPO positive. The corresponding percentage of anti-TPO positivity noted in the clinical hypothyroidism and subclinical hypothyroidism groups were 80 % and 50% respectively. Conclusions: Serum TSH and anti-TPO analyses are essential in determining the etiology of hypothyroidism and risk of progression to overt hypothyroidism in patients with subclinical.